2008
DOI: 10.1093/ageing/afn300
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas arthropathy in an older patient

Abstract: Background: septic arthritis caused by Pseudomonas aeruginosa is uncommon in the immunocompetent older population, despite its occurrence in younger patients with open injuries and in intravenous drug abusers. Case Report: here we report a case of septic arthritis caused by P. aeruginosa complicated by death in an older patient with recently treated Pseudomonas urinary tract infection. Discussion: the diagnosis of Pseudomonas septic arthritis is made on culturing the organism from synovial fluid aspirate. Conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 7 publications
(10 reference statements)
0
11
0
Order By: Relevance
“…Although septic arthritis caused by P aeruginosa is uncommon,1–3 there are documented cases in specific joints 1 4–6. The site most frequently affected by far is the knee 1 5.…”
Section: Discussionmentioning
confidence: 99%
“…Although septic arthritis caused by P aeruginosa is uncommon,1–3 there are documented cases in specific joints 1 4–6. The site most frequently affected by far is the knee 1 5.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas arthropathy in an older patient SIR-The case report by Keynes et al [1] published in Age and Ageing suggested that only one case of pseudomonas aeruginosa septic arthritis affecting elderly people is currently in existence in the literature. May I point out that, in addition to the one case mentioned by the author [2], there are several such cases in the literature as highlighted below.…”
Section: Letters To the Editormentioning
confidence: 99%
“…SIR-We have read with interest the article by Rowe et al [1] published in Age and Ageing and will like to make the following comments. There are people who do not get referred or assessed by orthoptist for various reasons.…”
Section: Visual Impairment Following Stroke: Do Stroke Patients Requimentioning
confidence: 99%
See 1 more Smart Citation
“…P. aeruginosa accounts for an absolute minority of all osteoarticular pathogens [1], and most reports are either case series involving around 20-30 cases [9][10][11][12][13] or even less [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Moreover, these reports subsume P. aeruginosa under other Gram-negative pathogens [9,12,13,19], including anaerobes [10,28], and lack adjustment for case mix [9,10,19,21].…”
Section: Introductionmentioning
confidence: 99%